Differential effects of integrase strand transfer inhibitors, elvitegravir and raltegravir, on oligodendrocyte maturation: a role for the integrated stress response - Roth, Lindsay M. (Glia, 2020)
Regardless of adherence to combined antiretroviral therapy, white matter and myelin pathologies persist in patients with HIV-associated neurocognitive disorders, a spectrum of cognitive, motor, and behavioral impairments. We hypothesized that antiretroviral therapy alters the maturation of oligodendrocytes which synthesize myelin. We tested whether specific frontline integrase strand transfer inhibitors would alter oligodendrocyte differentiation and myelination. To model the effect of antiretrovirals on oligodendrocytes, we stimulated primary rat oligodendrocyte precursor cells to differentiate into mature oligodendrocytes in vitro in the presence of therapeutically relevant concentrations of elvitegravir or raltegravir and then assessed differentiation with lineage specific markers. To examine the effect of antiretrovirals on myelination, we treated mice with the demyelinating compound cuprizone, for five weeks. This was followed by three weeks of recovery in absence of cuprizone, during which time some mice received a daily intrajugular injection of elvitegravir. Brains were harvested, sectioned and processed by immunohistochemistry to examine oligodendrocyte maturation and myelination. Elvitegravir inhibited oligodendrocyte differentiation in vitro in a concentration-dependent manner, while raltegravir had no effect. Following cuprizone demyelination, administration of elvitegravir to adult mice reduced remyelination compared with control animals. Elvitegravir treatment activated the integrated stress response in oligodendrocytes in vitro, an effect which was completely blocked by pretreatment with the integrated stress response inhibitor Trans-ISRIB, preventing elvitegravir-mediated inhibition of oligodendrocyte maturation. These studies demonstrate that elvitegravir impairs oligodendrocyte maturation and remyelination and that the integrated stress response mediates this effect and may be a possible therapeutic target.